Spectrum of Leprosy Patients with Clinico-Histopathological Correlation: A Hospital Based Study - Singh, Arjun; Gaur, R; Ambey, R (Asian Journal of Medical Sciences, 2013)
Introduction: Leprosy is a chronic granulomatous, infectious disease involving skin and peripheral nerves. It is present in various clinicopathological forms depending upon immune status of the patients. Histopathological examination of skin provides confirmatory diagnosis in suspected cases and gives indication of progression and regression of disease under treatment. Ridley and Jopling classification is used to classify leprosy. The objective of study was to identify the clinical pattern of leprosy and performed detail clinico- histopathological correlation in our institute. Method: The study was carried out on the skin biopsies received in between 2007-2010. Biopsies were fixed in 10% formalin, processed and stained with Hematoxylin and Eosin, modified Fite Ferraco and Ziehl-Neelsen stains. The predesigned Performa was used to record observation. The clinical diagnosis were correlated with histopathology in all 120 cases. Result: The age of the patients was ranged from 8 to 79 years with mean age of 36.38 years. The male to female ratio of patients was 1.5 to 1. The majority of cases 79 (65.8%) were in the age group of 21-50 years. Highest parity was observed in stable polar group TT 100%. Clinco-histopathological agreement was seen in 98 (81.67%) cases, 14 (11.67%) cases shows minor disagreement and 8 (6%) cases major disagreement. Conclusion: The clinical and histopathological features along with bacteriological index are useful than any single parameter in arriving definitive diagnosis and classification of the leprosy. Asian Journal of Medical Science, Volume-4 (2013), Pages 11-16 DOI: http://dx.doi.org/10.3126/ajms.v4i4.7997